Intercultural understanding after Wittgenstein - Carmona, Carla, 1982-; Pérez-Choco, David; Tejedor, Chon (Anthem studies in Wittgenstein., 2023)
This volume addresses, from a Wittgensteinian perspective, the philosophical question of how to understand other cultures. We approach this question in a manner that emphasises the connection between its epistemological, ethical and political aspects, bringing into discussion Wittgensteinian and other cultural and philosophical traditions, notably from the West African Yoruba community, Japan, China and India.--